The Ceremony of Mengket Rumah Mbaruetnik Karo, Langkat Regency: Semiotic Study - Sitompul, Laura Sesil Frida (Institute of Computer Science (IOCS), 2019)
This study aims to describe the stages of the mengket rumah mbaru ceremony, the form, function and meaning of the symbols contained in the mengket rumah mbaru ceremony. The theory used to analyze is the semiotic theory proposed by Charles Sanders Pierce. The method used in this research is descriptive method. The results obtained from this research are: (1) The stages of the Mbaru Rumah Mengket Ceremony, (2) The symbol form in the Mbaru Rumah Mengket Ceremony, consists of 4 categories of symbol distribution, namely traditional equipment symbols (Lambe, uis, piher rice, amak mbentar, kampil), food symbol (cimpa, dish of sipuluh dua), time symbol (morning, wari mehuli) and status marking symbols (kalimbubu, sukut, anak beru, puang kalimbubu), (3) symbol function found in the menget ceremony mbaru house,